2018
DOI: 10.1002/advs.201800406
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Nickel Nitride Enriched with Nitrogen Vacancies as a High‐Efficiency Electrocatalyst for Hydrogen Evolution

Abstract: Development of high‐performance and cost‐effective non‐noble metal electrocatalysts is pivotal for the eco‐friendly production of hydrogen through electrolysis and hydrogen energy applications. Herein, the synthesis of an unconventional nickel nitride nanostructure enriched with nitrogen vacancies (Ni3N1− x) through plasma‐enhanced nitridation of commercial Ni foam (NF) is reported. The self‐supported Ni3N1− x/NF electrode can deliver a hydrogen evolution reaction (HER) activity competitive to commercial Pt/C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(108 citation statements)
references
References 64 publications
2
96
0
1
Order By: Relevance
“…Plasma‐induced approach is a versatile technique for rapid and large‐scale treatment of various materials by use of plasma gases under the appropriate regulation of plasma frequency and temperature . However, the need of frequency and temperature and high cost of plasma as the disadvantages are always required in this plasma‐induced process.…”
Section: Synthesis Of Architectural Electrocatalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma‐induced approach is a versatile technique for rapid and large‐scale treatment of various materials by use of plasma gases under the appropriate regulation of plasma frequency and temperature . However, the need of frequency and temperature and high cost of plasma as the disadvantages are always required in this plasma‐induced process.…”
Section: Synthesis Of Architectural Electrocatalystsmentioning
confidence: 99%
“…Cu 2 S nanosheet arrays on Cu foam were also synthesized by a facile iodine dielectric barrier discharge plasma and an anion‐exchange reaction, presenting prominent electrocatalytic activity and persistent stability . Nickel nitride nanostructure enriched with nitrogen vacancies (Ni 3 N 1− x ) has been produced by plasma‐enhanced nitridation of commercial Ni foam, producing current density of 10 mA cm −2 at a low overpotential of 55 mV and a low Tafel slope of 54 mV per decade for HER . Thus, plasma‐induced approach is a promising synthetic route for the construction of nanoarrays with the desired component and architectural morphology.…”
Section: Synthesis Of Architectural Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a displays the linear sweep voltammogram (LSV) curves of Pt–Ni, Pt–Ni(N), Pt–Ni/Ni 4 N, and commercial Pt/C, in which Pt/C is used as reference. Clearly, the Pt–Ni(N) NWs exhibit an overpotential of 13 mV at the current density of 10 mA cm −2 , which is much better than Pt–Ni (22 mV), Pt–Ni/Ni 4 N (21 mV), and Pt/C (29 mV), and also represents the best alkaline HER catalytic activity among the ever‐reported HER catalysts (Table S1, Supporting Information) . Even at the high current of 50 mA cm −2 , the Pt–Ni(N) NWs still deliver a superior overpotential of 34 mV, suggesting its feasibility under high current operation (Figure S11, Supporting Information).…”
mentioning
confidence: 93%
“…However, the scarcity and high cost of platinum are the major factors to impede its industrial‐scale implementation of massive H 2 production from water reduction. Hence, numerous nonnoble‐metal materials including transition metals, transition metal dichalcogenides, carbides, borides, nitrides, phosphides, and their derivatives have been extensively investigated. Recently, it has been demonstrated that transition metal oxides (TMOs) and TMOs coupling with metallic transition metals benefit HER under alkaline conditions …”
Section: Introductionmentioning
confidence: 99%